A Toxicological Evaluation of Mango Leaf Extract (Mangifera indica) Containing 60% Mangiferin - Szakonyiné, Ilona Pasics; Vértesi, Adél; Hirka, Gábor; Clewell, Amy; Endres, John R.; Glávits, Róbert; Reddeman, Robin A.; Béres, Erzsébet (Journal of toxicology, 2019)
A battery of OECD- and GLP-compliant toxicological studies was performed on mango leaf extract (Mangifera indica) containing 60% mangiferin (MLE). No evidence of genotoxicity was found in a bacterial reverse mutation test (Ames). While evidence of clastogenic activity was noted in an in vitro chromosomal aberration test, an in vivo mammalian micronucleus test showed no findings up to the limit dose (2000 mg/kg bw). A 90-day repeated dose oral toxicity study was conducted in rats using doses of 0 (vehicle control), 500, 1000, and 2000 mg/kg bw/day. Based on the lack of mortality or toxic effects in the 90-day study, the NOAEL for MLE in Han:Wist male and female rats was determined to be 2000 mg/kg bw/day, the highest dose tested.